2020
DOI: 10.3386/w27237
|View full text |Cite
|
Sign up to set email alerts
|

The Persuasive Effect of Fox News: Non-Compliance with Social Distancing During the Covid-19 Pandemic

Abstract: We test for and measure the effects of cable news in the US on regional differences in compliance with recommendations by health experts to practice social distancing during the early stages of the COVID-19 pandemic. We use a quasi-experimental design to estimate the causal effect of Fox News viewership on stay-at-home behavior by using only the incremental local viewership due to the quasi-random assignment of channel positions in a local cable line-up. We find that a 10% increase in Fox News cable viewership… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(80 citation statements)
references
References 0 publications
9
69
2
Order By: Relevance
“…Trust in government sources (the CDC, the FDA, and local health departments) had a positive association with accurate knowledge about COVID-19, whereas trust in private sources and social networks had a negative association. Consistent with our findings, other studies have shown that private media sources distribute messages that can reduce public trust in scientific knowledge and health policies [28,29]. Several studies have shown that social networks can become a platform for the distribution of misinformation.…”
Section: Principal Findingssupporting
confidence: 92%
“…Trust in government sources (the CDC, the FDA, and local health departments) had a positive association with accurate knowledge about COVID-19, whereas trust in private sources and social networks had a negative association. Consistent with our findings, other studies have shown that private media sources distribute messages that can reduce public trust in scientific knowledge and health policies [28,29]. Several studies have shown that social networks can become a platform for the distribution of misinformation.…”
Section: Principal Findingssupporting
confidence: 92%
“…It is possible that those who do not have a strong media preference are more easily swayed by misleading information compared with those who trust and follow health messaging provided by more factual information sources like CNN. 18 Given that over half of our sample have equal or no preferences, this observation provided insight that biased and false health messaging provided by big media sources like Fox may affect not only its group of loyal viewers but also some broader audience who are indifferent in terms of information sources.…”
Section: Discussionmentioning
confidence: 93%
“…This observation matched previous literature. A study by Simonov et al 18 showed that an increase in Fox News viewership was associated with a reduction in the tendency to stay at home. A different study by Anderson used cellular mobility data and found that areas with a higher share of CNN viewers had a larger increase in the fraction of devices staying at home, whereas an increase in Fox News viewership was associated with a decrease in the share of devices staying at home.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the specific perspective of who is exposed to distance learning, however, our findings reveal clear disparities. Given that lower-income and/or non-white students already tend to fall behind academically, their greater exposure to school closures and distance learning may exacerbate socio-economic and racial/ethnic gaps in learning outcomes 13 In the context of the COVID-19 pandemic, SafeGraph data have frequently been applied to measure the share of a community's residents who appear to be social distancing or who appear to be engaged in full-time work [25][26][27][28][29][30] . For our purposes, we measure foot traffic to more than 100,000 schools across nearly every county in the U.S. to evaluate how the number of visits to each school in a given month in 2020 (say, December 2020) compares to the number of visits 12 months prior (December 2019).…”
Section: Discussionmentioning
confidence: 99%